Evaluation of a waistband for attaching external radiotransmitters to anurans. (21st July 2015) - Groff, Luke A.; Pitt, Amber L.; Baldwin, Robert F.; Calhoun, Aram J. K.; Loftin, Cynthia S.
ABSTRACT Radiotelemetry provides fine‐scale temporal and spatial information about an individual's movements and habitat use; however, its use for monitoring amphibians has been restricted by transmitter mass and lack of suitable attachment techniques. We describe a novel waistband for attaching external radiotransmitters to anurans and evaluate the percentages of resulting abrasions, lacerations, and shed transmitters. We used radiotelemetry to monitor movements and habitat use of wood frogs (Lithobates sylvaticus) in 2006 and 2011–2013 in Maine, USA; American toads (Anaxyrus americanus) in 2012 in North Carolina, USA; and, wood frogs, southern leopard frogs (L. sphenocephalus), and green frogs (L. clamitans) in 2012 in South Carolina, USA. We monitored 172 anurans for 1–365 days (56.4 ± 59.4) in a single year and 1–691 days (60.5 ± 94.1) across years. Our waistband resulted in an injury percentage comparable to 7 alternative anuran waistband attachment techniques; however, 12.5% fewer anurans shed their waistband when attached with our technique. Waistband retention facilitates longer monitoring periods and, thus, provides a greater quantity of data per radiotagged individual. © 2015 The Wildlife Society.